Design of perching mechanism for UAV - Lee, Wei Chong. (2012)
The variability of sizes and capabilities of UAVs allow them to conduct a myriad range of missions, of which surveillance takes up a great part. Research and development toward improving surveillance capabilities include extending mission life, by allowing the UAV to perch on locations such as tree branches, like birds.